Overcoming bias in Citrus tristeza virus (CTV) genotype detection and a population study of CTV within Southern African Star Ruby grapefruit orchards - Pietersen, Gerhard (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.